1988
DOI: 10.1111/j.1365-2621.1988.tb07840.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Properties of Raw and Heat Processed Cowpea (Vigna unguiculata, Walp) Flour

Abstract: The functional properties, gelation, water and oil absorption, emulsification, foaming and protein solubility of raw and heat processed cowpea flour were determined. The effects of pH and NaCl concentration on some of these functional properties were also investigated. Protein solubility vs pH profile showed minimal solubility at pH 4. Water and oil absorption capacities of raw flour were 2.4 g/g and 2.9 g/g, respectively, while heat processed flour gave 3.6 g/g and 3.2 gl g, respectively. Addition of NaCl up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
95
1
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(117 citation statements)
references
References 11 publications
19
95
1
2
Order By: Relevance
“…There is now evidence that dietary fibre has a number of beneficial effects related to its nondigestibility in the digestive tract (Asp 1996). The value of carbohydrate obtained in this study compares favourably with those reported for some varieties of cowpeas (Oke et al 1985;Abbey and Ibeh 1988). The calculated fatty acids and metabolizable energy values for the raw P. coccineus seeds were 5.5% and 1538.4 kJ 100 g…”
Section: Estimation Of Isoelectric Point (Pi) Quality Of Dietary Prosupporting
confidence: 72%
“…There is now evidence that dietary fibre has a number of beneficial effects related to its nondigestibility in the digestive tract (Asp 1996). The value of carbohydrate obtained in this study compares favourably with those reported for some varieties of cowpeas (Oke et al 1985;Abbey and Ibeh 1988). The calculated fatty acids and metabolizable energy values for the raw P. coccineus seeds were 5.5% and 1538.4 kJ 100 g…”
Section: Estimation Of Isoelectric Point (Pi) Quality Of Dietary Prosupporting
confidence: 72%
“…These values are comparable with those reported for chickpea (1.0-1.2 g/g), soybean (1.2 g/g), pigeon pea (1.2 ml/g), soybean meal (1.1 g/g), and great northern bean fl our (1.0 g/g) by Kaur and Singh (2005), Akubor (2007), Mizubuti et al (2000), Sharma and Subramanian (1994) and Sathe and Salunkhe (1981), respectively. Pawar and Ingle (1988), Dzudie and Hardy (1996), and Abbey and Ibeh (1988) reported OAC of 2.4 g/g in moth bean, 1.9 g/g in green mung bean, and 2.9 g/g in raw cowpea, respectively, which were higher than the values observed in the present study. Adebowale and Lawal (2004) reported that fl ours with good OAC are potentially useful in fl avor retention, improvement of palatability and extension of shelf life particularly in bakery or meat products where fat absorption is desired.…”
Section: Physico-chemical and Functional Propertiescontrasting
confidence: 56%
“…The differences in WAC between the fl ours can be attributed to their different protein and carbohydrate fractions. WAC of 2.2 g/g for soybean fl our (Akubor 2007), 1.3-1.5 g/g for chickpea fl our (Kaur and Singh 2005), 2.1 g/g in green mung bean fl our (Dzudie and Hardy 1996), 2.4 g/g for moth bean fl our (Pawar and Ingle 1988), 2.2 g/g for soybean meal (Sharma and Subramanian 1994) and 2.4 g/g for raw cowpea fl our (Abbey and Ibeh 1988) have been reported earlier. These WAC values, especially the high value of 'LL 699' fl our makes lentil fl ours as useful ingredients in the preparation of comminuted products and to improve handling characteristics of bread dough.…”
Section: Physico-chemical and Functional Propertiesmentioning
confidence: 99%
“…These values are in close agreement with those presented by Osei and Dei (1998, unpublished) and Dei Carmen et al (1999) and indicate that heating may generally slightly increase nutrient values as a result of the evaporation of water (Ahenkora et al, 1999). The crude protein content of MP compares favourably with that of chickpea, mung bean and several cowpea varieties (Hsu et al, 1977;Abbey and Ibeh, 1988). …”
Section: Resultssupporting
confidence: 81%